2007
DOI: 10.1303/aez.2007.89
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation of sweet potato weevils, Cylas formicarius (Fabricius) (Coleoptera: Brentidae), in main infested areas in the world based upon the internal transcribed spacer-1 (ITS-1) region

Abstract: Genetic variations of the internal transcribed spacer-1 region in sweet potato weevil, Cylas formicarius, were examined from 27 collection sites in the main infested areas in the world, except Africa, in this study. The ITS-1 lengths of 36 weevils tested in this study ranged from 557 to 587 bp, and were conspicuously longer in weevils from India. The genetic distances between weevils from India and from the other areas tested were larger than among weevils from the latter areas. The phylogenetic tree based on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
9
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 22 publications
3
9
0
Order By: Relevance
“…Our results are consistent with these findings as the F ST values that we found indicated low population differentiation. The studies of Kawamura et al (2002Kawamura et al ( , 2007 and our study demonstrate conclusively that diversity in these populations of C. formicarius elegantulus is low, which is consistent for an introduced pest. Mention of trade names or commercial products in this article is solely for the purpose of providing specific information and does not imply recommendation or endorsement by the University of Tennessee or the United States Department of Agriculture.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…Our results are consistent with these findings as the F ST values that we found indicated low population differentiation. The studies of Kawamura et al (2002Kawamura et al ( , 2007 and our study demonstrate conclusively that diversity in these populations of C. formicarius elegantulus is low, which is consistent for an introduced pest. Mention of trade names or commercial products in this article is solely for the purpose of providing specific information and does not imply recommendation or endorsement by the University of Tennessee or the United States Department of Agriculture.…”
Section: Discussionsupporting
confidence: 77%
“…Additionally, this heterozygote deficiency could be due to the presence of null alleles. Severe inbreeding could be the result of quarantine efforts that limit dispersal and also the strong integrated pest management (IPM) strategies that are used in quarantined counties within the sweetpotato The population structure (two clusters) that we found were attributed to multiple point introductions of the sweetpotato weevils within populations and dispersal history is discussed thoroughly by Kawamura et al (2007). The low diversity observed, and the heterozygote deficiency could also be explained by repeated inbreeding within populations and the effectiveness of quarantine efforts within the United States that is potentially limiting introduction of individuals from additional populations.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…One possible explanation might be the low genetic variation in the traits. Because C. formicarius is an invasive species (Kawamura et al 2007), founder population size in Japan will be small. The Japanese Plant Protection law has strictly prohibited carry-in of host plants of sweetpotato weevils from infested countries to Japan since 1952.…”
Section: Discussionmentioning
confidence: 99%
“…A possible factor influencing monomorphism in the Ogasawara Islands is the difference in its invasion source. Kawamura et al (2007) suggested that the sources of populations of the Ogasawara Islands differed from those of the Southwest Islands based upon differences in the nucleotide sequences of the internal transcribed spacer-1 region. C. formicarius in the Ogasawara Islands may have originated from a monomorphic population of elytral color or from a small number of BE weevils in a polymorphic population.…”
Section: Discussionmentioning
confidence: 99%